The issue with issues management: Considering the emotional and gendered core of issues. (September 2019) - Madden, Stephanie
Issues managers have power over defining issues and legitimizing their importance. While discussion has increased about organizations taking a stand on polarizing social issues, there remains a gap in the issues management literature on how to address stigmatized issues, particularly those with a gendered component. This article offers a revised set of issues motivators that better encompass the gendered and emotional components of issues and guiding questions to assist issues managers in ensuring that organizational policies and practices are more inclusive. Finally, the emotional underpinnings of all phases of the issue life cycle are considered.